Ductile behavior and excellent corrosion resistance of Mg-Zn-Yb-Ag metallic glasses. (15th November 2021) - Lu, Wenbing; He, Meifeng; Yu, Dan; Xie, Xiaoming; Wang, Hao; Wang, Shuai; Yuan, Chenggong; Chen, Aiying
Graphical abstract: Highlights: The addition of Yb to Mg-Zn-Yb-Ag metallic glasses leads to the formation of dense shear bands and toughness fossa structures, with a attendant increase in plasticity to 3.5%. The formation of the oxide film of Yb element on Mg-Zn-Yb-Ag metallic glasses prevents further corrosion of the substrate by chloride ions in electrochemical test. The formation of dense and homogeneous papillary corrosion products prevents further matrix degradation in the immersion test. Abstract: Magnesium-based metal glasses (MMGs) have broad application potential as bio-implant materials because of their disordered atomic structure, fine degradability, low elasticity modulus, and high strength. However, their low plasticity and poor corrosion resistance limit their application. In the present study, Mg-Zn-Yb-Ag metallic glasses were fabricated by injecting into a copper roller. The addition of trace amounts of ytterbium (Yb) and precious metal silver significantly improved the ductility of MMGs under bending and tensile loading. The results show that the amorphous alloy with 4 at% of Yb exhibits optimum specific strength mainly because of high-density coarsening shear bands. Electrochemical experiments, immersion test, and analysis of corrosion products by XPS and EDS after immersion showed that the amorphous alloy with 4 at% of Yb exhibits the greatest corrosion resistance among the four samples because of rare earth (Yb) oxide film. The addition of the appropriate amount of the rare-earth element Yb to amorphous Mg-based alloys can not only remarkably influence the alloy plasticity but also improve the alloy corrosion resistance, thereby increasing the alloy application prospects.